Development of an Integrated Biology Learning Module with Al-Qur’an Verses on Ecosystem Subject for Grade X at MAN 1 Banyumas - Nur Cholifatun Nisa; Mufida Nofiana (Bioedukasi: Jurnal Pendidikan Biologi, 2026)
This study aims to develop an integrated biology learning module incorporating Al Qur’an verses on the ecosystem subject for grade X and to determine the module’s feasibility. The research is of the Research and Development (RD) type, using the 4-D research model (Define, Design, Develop, and Disseminate). Data collection methods used questionnaires. The questionnaires used in the research were validation, practicality, and module readability questionnaires. Data analysis was done using the Gregory formula and supported by percentage techniques. The results of the validation test by subject-matter and religious experts yielded an overall average of 97.77%, a very high validity rating, and were deemed appropriate for use. The results of the practicality test by teachers had an overall average of 83%, indicating that the test was considered very practical. The suggestions from the expert validators and teachers included changes in font color, the addition of Al Qur’an verses, modifications to images, and the addition of questions. The results of the module readability test showed that students obtained an average of 93%, placing them in the very good category. The research concludes that the biology learning module on the ecosystem subject can be developed by integrating Al Qur’an verses and is highly feasible for experts, very practical for teachers, and easily readable for students.